The Strategic Role of Content Management in Building Competitive Advantage through Digital Marketing: A Study on SME Products - Fatmawaty , A. St.; Gayatri , I Gusti Agung Sasih (Smart International Management Journal, 2025)
This research investigates the structural relationship between Strategic Content Management and Competitive Advantage among SMEs in West Sumatra, specifically examining the mediating function of Digital Marketing Integration. Grounded in the Relational View Theory, the study utilizes official secondary data from BPS and KKP, analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM) to ensure robustness in handling non-normal distributions. The findings reveal that Strategic Content Management significantly impacts Digital Marketing Integration ( = .72; p < .001) and Competitive Advantage ( = .25; p = .002). Notably, Digital Marketing Integration is confirmed as a strong partial mediator with a Variance Accounted For (VAF) value of 75.3%. This empirical evidence underscores that the strategic value of internal content is effectively realized only through synchronized digital processes. This study advances the body of knowledge by clarifying the causal mechanisms that transform operational data into sustainable market dominance within the SME digital ecosystem.